Hubungan Kausalitas antara Fluktuasi Suku Bunga Kredit dan Pertumbuhan Kredit Modal Kerja pada Bank Persero Di Indonesia Periode 2010 - 2015 - Shantika, Fadhillah (Jurnal Ilmiah Mahasiswa FEB, 2016)
The purpose of this study is to investigates the relationship between the fluctuation of lending interest rate and working capital lending growth of Persero Bank in Indonesia for The Period 2010 - 2015. The analyticalÂ  method is Granger-Sims causality test because the data in this research has been stationary at the degree level.The result showed there was billateral causality between the fluctuation of lending interest rate and working capital lending growth of Persero Bank In Indonesia. Based on the results of these studies are expected to be a basic consideration for the the authority to establish a policy loan interest rate is appropriate so as to encourage optimal credit growth so that the government's aim to empower the business sector will be right on target.Keywords: Interest Rate, Credit Growth, Causality Test, Billateral Causality.